Pelatihan Strategi Penanganan Anak Berkebutuhan Khusus (ABK) Bagi Guru Paud - Septiyani Endang Yunitasari; Yuniliyanti; Rusmiyati; Triandy Ermawanti (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2024)
This community service activity aims to support and empower Early Childhood Education (PAUD) teachers in handling Children with Special Needs (ABK) in East Cikarang District, Bekasi Regency. Through this program, various practical and interactive activities are held, including intensive training, workshops, and mentoring sessions focused on implementing inclusive education strategies. Evaluation of this activity shows a significant increase in teachers' understanding and skills in supporting ABK, with understanding scores increasing from 45% on the pre-test to 68% on the post-test after the intervention. These results indicate that interventions based on adaptive learning strategies and collaboration between teachers and parents are very effective in increasing teachers' awareness and knowledge about ABK. This program enriches the learning experience for PAUD teachers and contributes to creating a more inclusive and responsive educational environment for ABK in the community.